Strain-engineered growth of two-dimensional materials - Geun Ho Ahn (Nature Portfolio, 2017)
Strain engineering is an essential tool for modifying local electronic properties in silicon-based electronics. Here, Ahn et al. demonstrate control of biaxial strain in two-dimensional materials based on the growth substrate, enabling more complex low-dimensional electronics.